The effect of using the algorithm of restrictive intraoperative fluid therapy, early immune enteral nutrition, and early patient mobilization on orthotopic liver transplantation outcomes - A. M. Dzyadz'ko; M. L. Katin; O. A. Chugunova; A. F. Minov; E. G. Oganova; E. O. Santotskiy; A. E. Shcherba; O. O. Rummo; I. I. Kanus (Трансплантология (Москва), 2016)
Major surgical procedures induce a number of pathophysiological responses, which may lead to a significant increase in perioperative complications, delayed recovery and rehabilitation, and longer hospital stays. Fast-track surgery, also known as enhanced recovery after surgery (ERAS) or as multimodal surgery, aims at decreasing the frequency of postoperative complications, creating optimal conditions for earlier postoperative recovery and return to normal life activities.The implementation of fast-track programs results in a reduced treatment duration without increase in readmissions. In this article, we have described our experience in the application of fast track program components to improve the outcomes after liver transplantation.